2019
DOI: 10.1101/744383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-termin vivoimaging ofDrosophilalarvae

Abstract: The Drosophila larva has been used to investigate many processes in cell biology, including morphogenesis, physiology, responses to drugs and new therapeutic compounds. Despite its enormous potential as a model system, it has technical limitations in cases where longer-term live imaging is necessary, because of the lack of efficient methods for immobilising larvae for extended periods. We describe here a simple procedure for anaesthetisation and long-term in vivo imaging of the epidermis and other larval organ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…C9100‐50; 1,000 × 1,000 pixels) controlled by Volocity v.6.3.57, with 488‐nm and 561‐nm channels. z‐stacks were taken with a step size of 0.28 μm with 60×/1.2 and 0.24 μm with 40×/1.3 (45–95 z ‐stacks, covering a 10–30‐μm depth) both for live and fixed specimens (Kakanj et al , 2020). All figures and videos show merged z ‐stacks.…”
Section: Methodsmentioning
confidence: 99%
“…C9100‐50; 1,000 × 1,000 pixels) controlled by Volocity v.6.3.57, with 488‐nm and 561‐nm channels. z‐stacks were taken with a step size of 0.28 μm with 60×/1.2 and 0.24 μm with 40×/1.3 (45–95 z ‐stacks, covering a 10–30‐μm depth) both for live and fixed specimens (Kakanj et al , 2020). All figures and videos show merged z ‐stacks.…”
Section: Methodsmentioning
confidence: 99%
“…Whole larval images were acquired on either a Zeiss SteREO Discovery.V12 (Zeiss Achromat S 0.63x FWD 107mm objective) and Zeiss AxioCam ICc 5 camera (images in Fig 1 ), or on a Leica MZ10 F stereoscope (Leica Plan APO 1.0x objective #10450028) and Zeiss AxioCam MRc r2.1 camera (images in Fig 2 ). To immobilize larvae for imaging, wandering L3 larvae were anesthetized using di-ethyl ether for 3.5 minutes as described in (Kakanj et al, 2020). Larval and adult tissues were prepared for imaging by dissecting in 1x PBS, fixing in 1x PBS, 3.7% paraformaldehyde, 0.3% Triton-X for 30 minutes, and staining with Hoechst 33342 (1:1,500, Life Technologies, Carlsbad, CA, #c10339).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we investigated whether ubi-Gal4 MagHigh could be used to activate gene expression in 3 rd instar larvae. By adapting a protocol for imaging anesthetized larvae (Kakanj et al, 2020), we found that multiphoton illumination turned on His2B:RFP expression in a ROI of the wing disc pouch (Figures S3B and S3C). Furthermore, by specifically photoactivating the presumptive notum region of one of the two wing imaginal discs, we recovered strong His2B:RFP expression in the corresponding pupal hemi-notum, illustrating the possibility of gene activation on one side of the animal (Figures 3C and 3D).…”
Section: Shinegal4 Is Effective In Multiple Tissues and At Different Life Cycle Stagesmentioning
confidence: 99%
“…After 3 washes in PBS, embryos were placed on a MatTek dish (MatTek Life Sciences) and covered with PBS for live imaging. Larva For two photon activation experiments, we adapted the method described in (Kakanj et al, 2020) to anesthetize and mount living larvae for tissues imaging in order to perform small-scale experiments and increase viability at pupal stage. Briefly, using a red light in a dark room, 7 to 8 third instar larvae were collected with a soft brush, and placed in small homemade plastic cages allowing vapor exchange (see Figure 4 (Kakanj et al, 2020)).…”
Section: Ll Open Accessmentioning
confidence: 99%